Measuring emission rates of particulate matter from fan ventilated swine barns - Predicala, B.Z.; Maghirang, Ronaldo G. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Methods for measuring concentrations and emission rates of particulate matter (PM) from mechanically ventilated livestock buildings were evaluated in a laboratory facility and in a swine-finishing barn. Concentrations of PM were measured inside the room (room sampling) and at the exhaust duct (exhaust sampling). Concentrations at the exhaust duct were determined using high-volume traverse downstream of the exhaust fan, low-volume traverse downstream of the fan, and fixed sampling upstream and downstream of the fan. The traverse methods, which served as the reference, were conducted under isokinetic conditions; fixed sampling was done under both isokinetic and sub-isokinetic conditions. Compared to the traverse method, both room sampling and exhaust sampling under subisokinetic conditions overestimated PM concentrations. Fixed sampling under isokinetic conditions, on the other hand, did not differ significantly (P>0.05) from the high-volume traverse method. Thus, isokinetic fixed sampling can be an alternative to the more expensive and time-consuming high-volume PM traverse method to measure PM concentrations and emission rates at the exhaust.
Keywords: Swine; Air quality; Dust; Emission; Measurement